EDITORIAL FOREWORD Psychosophia Vol. 2, No. 1 (2020) - Oktarizal Drianus (Department of Islamic Psychology, The State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, Indonesia, 2020)
Today, we live in social and religious life that it was undergoing rapid changes. This drastic change in the transformation era affects people's thoughts, beliefs, attitudes, and behavior in harmonizing their lives. Psychosophia: Journal of Psychology, Religion, and Humanity captures this important issue. Therefore, this volume explores several issues in psychological dynamics that live in this fast-rapid-chaotic life.